ACUTE APPENDICITIS-LAPAROSCOPIC APPENDECTOMY AND REASONS FOR CONVERSION - Konstantin Kostov (Peytchinski Publishing, 2020)
Purpose: The purpose of this study is to analyze the efficacy of laparoscopic appendectomy, its advantages and disadvantages and the cause of conversion in patients with acute appendicitis. Material and Methods: Data from 128 patients with acute appendicitis, operated laparoscopically, was processed by a retrospective clinical analysis for the period of 1.5. 2017 to 31.12. 2017 in the General, Visceral and Emergency Surgery Section of the UMHATEM "Pirogov". Of the hospitalized, women were 73 (57.03%), men 55 (42.97%). The age in this retrospective analysis varied from 18 to 74 years (average 35.2 years). Results: The laparoscopy time interval was 27-119 minutes. The conversion included a total of 10 cases (7.81%). The hospital stays varied from 2 to 7 days. Morbidity rate was 4.69%. Mortality- 0% Conclusions: Laparoscopic approach has been identified as a method of choice in patients with acute appendicitis because of advantages of low levels of morbidity, the diagnosis and treatment of accidentally discovered other pathological findings, the earlier return to normal activity, the excellent cosmetic results and the reduced postoperative therapy.